Use of simulated experiments for material characterization of brittle materials subjected to high strain rate dynamic tension. (28th January 2017) - Lukić, Bratislav; Saletti, Dominique; Forquin, Pascal
Abstract : Rapid progress in ultra-high-speed imaging has allowed material properties to be studied at high strain rates by applying full-field measurements and inverse identification methods. Nevertheless, the sensitivity of these techniques still requires a better understanding, since various extrinsic factors present during an actual experiment make it difficult to separate different sources of errors that can significantly affect the quality of the identified results. This study presents a methodology using simulated experiments to investigate the accuracy of the so-called spalling technique (used to study tensile properties of concrete subjected to high strain rates) by numerically simulating the entire identification process. The experimental technique uses the virtual fields method and the grid method. The methodology consists of reproducing the recording process of an ultra-high-speed camera by generating sequences of synthetically deformed images of a sample surface, which are then analysed using the standard tools. The investigation of the uncertainty of the identified parameters, such as Young's modulus along with the stress–strain constitutive response, is addressed by introducing the most significant user-dependent parameters (i.e. acquisition speed, camera dynamic range, grid sampling, blurring), proving that the used technique can be an effective tool for error investigation. This article is part of the themed issue 'Experimental testing and modelling of brittle materials at high strain rates'.